CGIAR Platform for Big Data in Agriculture - Inspire Challenge Review (2017-2020) - Mockshell, Jonathan; Nielsen Ritter, Thea; Asante-Addo, Collins; Ankamah-Yeboah, Isaac; Wong, Kelvin (CGIAR Platform for Big Data in Agriculture, 2021)
This report provides evidence-based insights about the state of digital agricultural innovations through the eyes of the Inspire Challenge, which can help design and support future Digital Agricultural Innovation System (DAIS) in the One CGIAR. The results show that the first phase of the Inspire Challenge program was successful at serving as a DAIS enabler by creating partnerships in the digital agricultural ecosystem, which led to digital innovations in food systems.